A credit to your clinic: steps practitioners can take towards a good report. (2nd September 2020) - Bernstein, Adam
Abstract : Having a good credit report can make all the difference when it comes to sourcing commercial funding or being granted good terms from suppliers. Adam Bernstein looks at the steps that clinics can take to improve their standing.